Power Engineering under the Guise of Nutrition: A Critical Analysis of Badan Gizi Nasional Formation - Fikri, Sultoni; Hikam, Reza Maulana (TRUNOJOYO LAW REVIEW, 2025)
Presidential Regulation No. 83 of 2024 was enacted under the pretext of addressing the critical issue of national nutrition. However, beneath the technocratic narrative and the sterile legal language, there are strong indications that this regulation conceals a deeper political-economic agenda. This study aims to examine whether the establishment of the National Nutrition Agency is a purely administrative response or a covert instrument of power hegemony. The contribution of this study lies in uncovering how a seemingly neutral policy on nutrition governance operates as a mechanism of executive aggrandisement. By applying a Critical Legal Studies framework, this research advances the understanding of how legal instruments can embed and normalise political centralisation under the guise of public health policy. This area remains underexplored in Indonesian legal scholarship. The methodology employed is a juridical-critical approach based on Critical Legal Studies, which involves a normative analysis of the regulation's content and its relationship to relevant laws and regulations. The study's findings reveal that the BGN has an expansive authority structure directly under the President, creating a potential for vertical control over the distribution of national nutrition resources. Furthermore, there is a potential overlap with other agencies (such as Bapanas, the Ministry of Health, and the Ministry of Social Affairs), weak oversight mechanisms, and the potential normalisation of power expansion through administrative law. In this context, the law is no longer an instrument of justice, but rather a tool of political legitimisation within a technocratic framework. This study recommends an institutional evaluation of the BGN and strengthening of legislative control over the expansion of executive bodies.